Neuroprotective Role of Nigella Sativa on Methamphetamine induced Hippocampal Injury in Male Albino Mice - Rajpar, Farhana; Memon, Samreen; Goswami, Pushpa; Rajpar, Fayaz Ali (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To evaluate the neuroprotective effects of Nigella sativa in methamphetamine induced hippocampal injury. METHODOLOGY: This Experimental study was conducted at Department of Anatomy, Liaquat University of Medical and Health Sciences (LUMHS), Jamshoro, in collaboration with Sindh Agriculture University Tandojam from April 2016 to September 2016 on sixty adult male mice of average 25-40gms. All the animals were housed properly, fed on lab chow and tap water ad libitum. The mice were divided into group A (control), B, C and D were experimental groups. Group A was given normal saline orally at the volume of 1 ml/kg. Group B animals were given METH at volume of 10 mL/kg containing 10.0 mg/kg METH. Group C animals were given Kalonji extract at the volume of 3mg/ml of extract, and Group D animals were given METH plus Kalonji extract at the same volume and dose as mentioned earlier. The animals were sacrificed by cervical dislocation after one week of last injection. Brain of each animal was removed, immersed in 10% formaldehyde solution for microscopic studies. RESULTS: The weight of different groups at baseline was equal in all groups which is reduced at the end of study period. METH treated mice showing hyper cellularity of different layers, in contrast of N.S + METH treated mice showing marked decrease in cellularity of hippocampus. CONCLUSION: The findings of above study shows neuroprotective effect of Nigella sativa against methamphetamine induced cell injury in hippocampus of mice model.